204k views
0 votes
If f(x) = x2 − 6x + 3 x − 1 , what is f(−1)? A) −5 B) −2 C) 2 D) 5

User Mcatis
by
5.3k points

2 Answers

4 votes

Answer:

f(-1)=3

Step-by-step explanation:

f(x)=x^2-6x+3x-1

f(x)=x^2-3x-1

f(-1)=(-1)^2-3(-1)-1

f(-1)=1+3-1

f(-1)=4-1

f(-1)=3

User Jnd
by
5.2k points
3 votes

Final answer:

To find f(-1) for the given function f(x) = x^2 - 6x + 3 / (x - 1), substitute -1 for x and simplify the expression to calculate the result. The result of f(-1) is -5, which corresponds to option A.

Step-by-step explanation:

The student has asked to find the value of the function f(x) when x is equal to -1. The function is given as f(x) = x2 − 6x + 3 / (x − 1). To find f(-1), we substitute x with -1 in the equation and perform the necessary arithmetic operations.

First, we replace x with -1:

f(-1) = (-1)2 − 6(-1) + 3 / ((-1) − 1)

This simplifies to:

f(-1) = 1 + 6 + 3 / (-1 - 1)

Further simplifying, we get:

f(-1) = 10 / -2

Finally, we can see that f(-1) equals to:

f(-1) = -5

Therefore, the correct answer is A) − 5.

User Alonad
by
5.6k points